Ultrasonographic evaluation of urinary bladder neoplasias - Patidar, Nipa; Desai, Ekta; Goyani, Bhavesh; Sastri, Mona (International Journal of Research in Medical Sciences, 2017)
Background: Ultrasound has been shown to be a sensitive method for evaluating patients with chronic obstruction, bladder outlet obstruction, urinary tract infection, renal failure, renal and bladder neoplasm and renal transplants. It is now recommended as the method of choice for preliminary assessment and follow-up of several of these disorders. The objective of the study was to evaluate the specificity and sensitivity of ultrasonographic features of neoplastic lesions of urinary bladder. Methods: Clinical impression about the suspected abnormality was obtained from the case papers or from referring by clinical colleagues. Data was recorded under headings like clinical history, clinical examinations, investigations like urine analysis, serum creatinine and blood urea, X-ray of chest and Kidney Urinary Bladder, pelvic and abdominal Ultrasonography, and if require CT scan and guided biopsy. Results: out of total 35 cases 29 were Transitional Cell Carcinoma, 4 were Squamous Cell Carcinoma, One leiomyoma and one was secondary from bronchogenic carcinoma. Most of tumours were irregular in shape in both TCC and SCC patients. Most of tumour showed heterogeneous echo-texture in ultrasonography. While all SCC showed heterogeneous with calcification echo-texture. Most of the cases had residual urine volume was less than 100 cc. Conclusions: The primary advantage of ultrasound over the conventional study was found to be its ability to detect focal or diffuse bladder wall abnormalities in patients who presented with commonest complaint of painless hematuria.